1997
DOI: 10.1111/1467-8659.16.3conferenceissue.35
|View full text |Cite
|
Sign up to set email alerts
|

The Personal Interaction Panel – a Two‐Handed Interface for Augmented Reality

Abstract: This paper describes the introduction of a new interaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 17 publications
0
64
0
3
Order By: Relevance
“…Wearable sensor technologies are prone to noise and may not be capable of precise tracking with a high level of reliability in all environments. Furthermore, users may have difficulty performing very precise gestures without a haptic surface for feedback [199]. One further drawback of hand input is fatigue, likely to result from large motions over an extended duration without an appropriate resting surface.…”
Section: Direct and Indirect Input Methods For Saismentioning
confidence: 99%
See 4 more Smart Citations
“…Wearable sensor technologies are prone to noise and may not be capable of precise tracking with a high level of reliability in all environments. Furthermore, users may have difficulty performing very precise gestures without a haptic surface for feedback [199]. One further drawback of hand input is fatigue, likely to result from large motions over an extended duration without an appropriate resting surface.…”
Section: Direct and Indirect Input Methods For Saismentioning
confidence: 99%
“…Stereoscopic displays (i.e. Caves, some HWDs) often use intangible, virtual surfaces, although information spaces are sometimes intentionally set to coincide with physical surfaces [199]. In free space, researchers have found that indirect input is faster, less fatiguing and more stable [6,94,205] than direct input.…”
Section: Tangibility Tangible Intangiblementioning
confidence: 99%
See 3 more Smart Citations